Developing a pop up book supportive to narrative-texts teaching - Khoirunnisa Safitri; Sudarsono Sudarsono (UPT Bahasa Universitas Tanjungpura, 2019)
This research aims to develop Pop-Up Book as supplementary media to support the teaching of narrative texts and to evaluate whether or not the media are feasible to teach narrative texts to the tenth grade students of SMA Negeri 8 Pontianak. The media consisted of narrative texts with pop-up pictures. They were divided based on the structure of a narrative text. The materials were taken from the students’ textbook that the researcher has simplified. The procedures were adapted from ADDIE Model proposed by Branch and it used three phases, namely, Analyse, Design, and Develop. From analyse phase, it was found that the students needed interesting media that was visually attractive to engage them in the teaching learning process and to support the existing materials. The Design phase covered the aspects, which were the focus of the media, of the materials and the pictures for the media, and the structure of the media. The Development phase concerned the development of the essential parts of the media. According to the evaluation result, the media are considered feasible to be applied by the teachers to teach narrative text reading.